Correction to: Gender inequality in the health workforce in the midst of achieving universal health coverage in Mexico - Julio César Montañez-Hernández; Jacqueline Elizabeth Alcalde-Rabanal; Gustavo Humberto Nigenda-López; Gladis Patricia Aristizábal-Hoyos; Lorena Dini (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.